Asia prostate cancer study (A-CaP Study) launch symposium - Akaza, Hideyuki (Prostate Int, 2016)
The Asian Prostate Cancer (A-CaP) Study is an Asia-wide initiative that has been developed over the course of 2 years. The A-CaP Study is scheduled to begin in 2016, when each participating country or region will begin registration of newly diagnosed prostate cancer patients and conduct prognosis investigations. From the data gathered, common research themes will be identified, such as comparisons among Asian countries of background factors in newly diagnosed prostate cancer patients. This is the first Asia-wide study of prostate cancer and has developed from single country research efforts in this field, including in Japan and Korea. The inaugural Board Meeting of A-CaP was held on December 11, 2015 at the Research Center for Advanced Science and Technology, The University of Tokyo, attended by representatives of all participating countries and regions, who signed a memorandum of understanding concerning registration for A-CaP. Following the Board Meeting an A-CaP Launch Symposium was held. The symposium was attended by representatives of countries and regions participating in A-CaP, who gave presentations. Presentations and a keynote address were also delivered by representatives of the University of California San Francisco, USA, and the Peter MacCallum Cancer Centre, Australia, who provided insight and experience on similar databases compiled in their respective countries.